Antimicrobial stewardship in Australia: the role of qualitative research in programme development. Issue 4 (18th November 2021) - Thursky, Karin A; Hardefeldt, Laura Y; Rajkhowa, Arjun; Ierano, Courtney; Bishop, Jaclyn; Hawes, Lesley; Biezen, Ruby; Saha, Sajal K; Dowson, Leslie; Bailey, Kirsten E; Scarborough, Ri; Little, Stephen B; et al.
Abstract: Antimicrobial stewardship (AMS) in Australia is supported by a number of factors, including enabling national policies, sectoral clinical governance frameworks and surveillance programmes, clinician-led educational initiatives and health services research. A One Health research programme undertaken by the National Centre for Antimicrobial Stewardship (NCAS) in Australia has combined antimicrobial prescribing surveillance with qualitative research focused on developing antimicrobial use-related situational analyses and scoping AMS implementation options across healthcare settings, including metropolitan hospitals, regional and rural hospitals, aged care homes, general practice clinics and companion animal and agricultural veterinary practices. Qualitative research involving clinicians across these diverse settings in Australia has contributed to improved understanding of contextual factors that influence antimicrobial prescribing, and barriers and facilitators of AMS implementation. This body of research has been underpinned by a commitment to supplementing 'big data' on antimicrobial prescribing practices, where available, with knowledge of the sociocultural, technical, environmental and other factors that shape prescribing behaviours. NCAS provided a unique opportunity for exchange and cross-pollination across the human and animal health programme domains. It has facilitated synergistic approaches to AMS research and education, and implementation of resources and stewardship activities. The NCAS programme aimed to synergistically combine quantitative and qualitative approaches to AMS research. In this article, we describe the qualitative findings of the first 5 years.